Open season 3 [videorecording (DVD)] - Cameron, Cody; Glover, Crispin; Stoller, Fred; Engel, Georgia; Schirripa, Steven R.; Cameron, Cody (Sony Pictures Home Entertainment, 2011)
When Boog's pals choose family obligations over the annual guys' trip, a disappointed Boog takes a trip on his own, which leads him right into the middle of a circus ring. When he switches places with a devious circus grizzly and falls for a troupe member, he'll come to realize that maybe you don't have to choose between family and friendship after all. Bonus features include a progression reel, and a Runaway RV game.